The Institutionalisation of The Democrat Party in The Face Of Electoral Contestation in The 2024 Elections Province East Nusa Tenggara - Apolonaris Gai; Kushandajani Kushandajani; Laila Kholid Alfirdaus; Nunik Retno Herawati (Jurnal Studi Sosial dan Politik, 2024)
This study aims to describe the Institutionalisation of the Democratic Party Facing Electoral Contestation for the 2024 Elections in East Nusa Tenggara Province. This research uses qualitative research methods. Data were collected using documentation, interviews, and direct observation techniques. The results of this study indicate that the institutionalization of the Democratic Party in facing the 2024 electoral contestation in East Nusa Tenggara has not achieved maximum results in realizing the strengthening of the institutionalization of the Democratic Party in East Nusa Tenggara Province for several reasons. This study finds that the biggest obstacle is funding, which is often minimal, while there are many consolidations and other activities. It can be concluded that if there are activities, contributions from members of the DPR RI / DPRD Province / Regency / City and the spontaneity of administrators/cadres when there are party activities are relied upon. Due to the Party's increasingly tricky internal financial conditions, contributions from administrators/members, mandatory contributions from cadres in the legislature, and executive and incidental donations, we unconsciously create pragmatic dependence. This results in the independence of the Party in making a decision. This condition implies that donors can take over or control the Party in various ways, including seizing the leadership through the internal funding conditions experienced by the Party.